More than Meets the Eye: Functionally Salient Changes in Internal Bone Architecture Accompany Divergence in Cichlid Feeding Mode. (15th May 2012) - Albertson, R. Craig; Cooper, W. James; Mann, Kenneth A.
Abstract : African cichlids have undergone extensive and repeated adaptive radiations in foraging habitat. While the external morphology of the cichlid craniofacial skeleton has been studied extensively, biomechanically relevant changes to internal bone architecture have been largely overlooked. Here we explore two fundamental questions: (1) Do changes in the internal architecture of bone accompany shifts in foraging mode? (2) What is the genetic basis for this trait? We focus on the maxilla, which is an integral part of the feeding apparatus and an element that should be subjected to significant bending forces during biting. Analyses of μ CT scans revealed clear differences between the maxilla of two species that employ alternative foraging strategies (i.e., biting versus suction feeding). Hybrids between the two species exhibit maxillary geometries that closely resemble those of the suction feeding species, consistent with a dominant mode of inheritance. This was supported by the results of a genetic mapping experiment, where suction feeding alleles were dominant to biting alleles at two loci that affect bone architecture. Overall, these data suggest that the internal structure of the cichlid maxilla has a tractable genetic basis and that discrete shifts in this trait have accompanied the evolution of alternate feeding modes.